Clinical status of permanent first molars in children aged seven to ten years in a Brazilian rural community - Lara Jansiski Motta; Joyce Garcia dos Santos; Thays Almeida Alfaya; Carolina Cardoso Guedes; Camila Haddad Leal de Godoy; Sandra Kalil Bussadori (Universidade Estadual de Campinas, 2015)
Aim: To evaluate the clinical status of permanent first molars and associations with dental caries, gingival bleeding, dental fluorosis and malocclusion. Methods: An observational study was carried out in a rural community denominated Morro do Saboó in the city of São Roque, state of São Paulo, Brazil. A total of 194 children aged seven to ten years were examined for dental caries using the index proposed by the World Health Organization. Other conditions were determined using the Gingival Alterations Index, Dean's Index and Dental Aesthetic Index. The chi-squared test was used for the statistical analysis of the data. Results: A total of 85.5% of the sample exhibited gingival bleeding and 69.9% exhibited malocclusion. A total of 53.6% had a clinical aspect of normality with regard to dental fluorosis. There was a predominance of sound teeth in the upper arch and teeth with carious lesions in the lower arch. No significant differences were found between sexes regarding gingival bleeding, dental fluorosis or malocclusion. Significant associations were found between tooth status and oral alterations (gingival bleeding, malocclusion and fluorosis) in teeth 16, 26 and 46 and between tooth status and gingival bleeding in tooth 36 (p<0.001). Conclusions: Caries activity in the permanent first molars was mainly associated with dental fluorosis and malocclusion. Strategies aimed at health promotion should be adopted on a large scale to minimize the prevalence of oral diseases.